MEKANISME INTERNAL DAN EKSTERNAL CORPORATE GOVERNANCE DALAM MEMITIGASI FINANCIAL DISTRESS (Studi Terhadap Perusahaan Manufaktur yang Terdaftar pada Bursa Efek Indonesia Periode 2011-2015) I - Irma Yanti; Meinarni Asnawi; Aaron M. A Simanjuntak (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2018)
This study examines whether internal and external corporate governance (CG) mechanisms can reduce the distressed financial pressures in Indonesian manufacturing industry. As a consideration,This research was investigated whether the internal mechanisms of CG, represented by independent committees as well as audit committee characteristics, and CG's external mechanisms whichdemonstrated by audit quality, have a negative relationship with distressed financial pressures on the manufacturing industry on the Indonesia Stock Exchange. Samples were obtained from 64 manufacturing companies with purposive sampling as a sampling method, and they were collectedof 320 company observations from 2011 to 2015 as samples. Data were obtained from the Company's Annual Report published by the Indonesia Stock Exchange from 2011 to 2015 as well as from the respective company's website. By using logistic regression analysis, this research shows that audit committee characteristics have a significant effect on the financial distress. However, there is no significant effect on the relation between Independent commissioners and audit quality.